2023
DOI: 10.3389/fimmu.2022.1011617
|View full text |Cite
|
Sign up to set email alerts
|

A 31-plex panel for high-dimensional single-cell analysis of murine preclinical models of solid tumors by imaging mass cytometry

Abstract: Currently, the study of resistance mechanisms and disease progression in cancer relies on the capacity to analyze tumors as a complex ecosystem of healthy and malignant cells. Therefore, one of the current challenges is to decipher the intra-tumor heterogeneity and especially the spatial distribution and interactions of the different cellular actors within the tumor. Preclinical mouse models are widely used to extend our understanding of the tumor microenvironment (TME). Such models are becoming more sophistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…For these reasons, IMC has been widely used in many studies aimed at dissecting the composition of different types of human cancer [21,22]. By contrast, only a few studies report the use of IMC in preclinical models of diseases [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, IMC has been widely used in many studies aimed at dissecting the composition of different types of human cancer [21,22]. By contrast, only a few studies report the use of IMC in preclinical models of diseases [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…These studies are particularly interesting since they facilitate the development of IMC applications in the oncology field by providing panels of antibodies usable for IMC analysis [44][45][46][47]. However, this technique has been mostly applied to human samples and only a few studies reported the use of IMC technology on mouse models of carcinogenesis [23,26]. To our knowledge, this is the first study reporting the validation of an IMC antibody panel for the investigation of a mouse model of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cell segmentation was performed as previously described ( 49 ). Briefly, pixel classification and training were performed using Ilastik v1.3.3 to generate a probability map.…”
Section: Methodsmentioning
confidence: 99%
“…The principle of the assay has been described previously [28]. Tissue labeling and data acquisition using the Hyperion Imaging System (Standard Biotools, San Francisco, CA, USA) were performed following the manufacturer's instructions, as described previously [29]. Further details are provided in Supplementary materials and methods.…”
Section: Imaging Mass Cytometrymentioning
confidence: 99%